Performance of immunohistochemistry as a useful tool for the diagnosis of cutaneous leishmaniasis in Panama, Central America. (August 2019) - Gonzalez, K.; Calzada, J.E.; Díaz, R.; Paz, H.; García, V.; Miranda, A.; Tomokane, T.; Puga, S.; Saldaña, A.; Laurenti, M.
Abstract: Cutaneous leishmaniasis (CL) is one of the most frequent parasitic zoonoses in Panama. Currently, conventional, molecular and histopathological tests are performed to diagnose CL. Immunohistochemistry (IHC) has proven to be a valuable tool to facilitate the diagnosis of leishmaniasis and to study the cellular immune response developed during the infection. Therefore, considering the absence of IHC in the diagnostic routine in Panama, the objective of this study is to demonstrate the usefulness of this test as a complementary diagnostic tool for improving the sensitivity of histopathology (HP) and helping to study the cellular immune response of patients. Samples from patients with suspected CL were analysed by intradermal reaction of Montenegro (IDRM), smears, culture, PCR ( Viannia, Hsp-70), HP and IHC. According to the diagnostic criteria, 95.8% of patients were positive for Leishmania sp., that was characterized as Leishmania (V.) panamensis by PCR-HSP70/RFLP. From positive samples, Leishmania was detected by the tested diagnostic methods in the following degrees: 100% by IDRM, 60% by smears, 93.3% by culture, 100% by kDNA PCR, 78.3% by PCR Hsp-70, 50% by HP and 73.9% by IHC. Although IHC had a poor correlation (k = 0.191) with the diagnostic criteria, the sensitivities of both HP (76.1%) and smears (89.1%) were improved by combining them with IHC. IHC considerably improved the detection of the Leishmania parasites in the histopathological sections, supporting the need to implement this diagnostic tool in Panama. In addition, immunohistochemistry allows evaluation of the patient's immune response and thus provides new guidelines for the treatment and control of CL in Panama. Highlights: The IHC is a valuable tool to complement the diagnosis of CL in Panamá. The IHC can improves the sensitivity of the histopathology diagnosis of CL. The use of combined methodologies is recommended to have a better diagnosis of CL.